Identifying key genes of classic papillary thyroid cancer in women aged more than 55 years old using bioinformatics analysis - Li, Chang-Chun; Ullah, Muhammad Hasnain Ehsan; Lin, Xiao; Shan, Su-Kang; Guo, Bei; Zheng, Ming-Hui; Wang, Yi; Li, Fuxingzi; Yuan, Ling-Qing (Frontiers in Endocrinology, 2022)
Background The incidence rate of thyroid carcinoma (THCA) markedly increased in the recent few decades and has been likely over-diagnosed, especially papillary thyroid cancer (PTC) in women. However, the incidence of advanced-stage papillary thyroid cancer is also rising. According to earlier studies, tumors with identical pathology might have different clinical outcomes, which implies some variances in papillary thyroid cancer. Although the mortality of thyroid cancer has remained stable or declined, there is still an important problem in estimating whether it is benign or needs surgery for patients with papillary thyroid cancer. Methods After obtaining data from The Cancer Genome Atlas (TCGA) Project-THCA database by R package TCGA bio links, 18 samples (11 at stage IV as high-risk group and 7 at stage I as low-risk group) were obtained using survival package and edgeR to ensure differential expression; ClusterProfiler package was used to carry on gene set enrichment analysis and searched the possible pathways in the Kyoto Encyclopedia of Genes and Genomes (KEGG) database. STRING and Cytoscape were used to construct and modify the protein–protein interaction (PPI) network to get hub genes of differentially expressed genes. Next, the pROC package was used to get the receiver operating characteristic (ROC) curves of hub genes’ disease-free survival (DFS). Then, transcription factors (TFs) and miRNAs of key genes were predicted by ENCORI and AnimalTFDB. In the end, TF–target genes–miRNA regulatory network was also constructed by Cytoscape. Results Our research obtained the top 9 candidate genes from the whole network (IFNA1, MRC1, LGALS3, LOX, POSTN, TIMP1, CD276, SDC4, and TLR2). According to the ROC results, TIMP1, LOX, CD276, IFNA1, TLR2, and POSTN were considered to play a more critical role in malignant papillary thyroid cancer or immature cancer of papillary thyroid cancer. Our analysis concludes that TIMP1, LOX, CD276, IFNA1, TLR2, and POSTN are identified as thyroid cancer biomarkers, which lead to the different clinical courses of a woman older than 55 years old with papillary thyroid cancer. Especially CD276, POSTN, and IFNA1 may be considered as new biomarkers associated with the prognosis of thyroid cancer. Conclusions TIMP1, LOX, CD276, IFNA1, TLR2, and POSTN have different expressions in PTCs, which lead to the various clinical courses of a woman older than 55 years old with papillary thyroid cancer. Especially CD276, POSTN, and IFNA1 may be considered as new potential biomarkers associated with the prognosis of thyroid cancer. In addition, TF–miRNA–target gene regulatory network may help further reach for PTC.